(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2015)
The article presents the methodological approaches and practical recommendations on the formation and implementation of crisis management system based on diversification of activities of service sector enterprises. The methodical approach to the evaluation of a crisis management system of service sector enterprises is proposed